The added worker effect in South Africa - Hoffman, Morne (School of Economics, 2020)
The theory that married women’s labour supply increases in response to their partners job loss is known as the added worker effect (addWE). This paper investigates how married women’s labour force participation, probability of employment and average working hours respond to the recently unanticipated job loss of their partners in South Africa. It also considers the effect of partners job loss on married women’s preference to work and the probability that they work more hours from the previous period. The paper finds that the probability of married women’s participation, employment and average working hours rises (a positive effect) in response to their partners unanticipated job loss. However, these results are all statistically insignificant and its inconclusive evidence can be attributed primarily to limitations in the data. Alternatively, the labour supply responses are modelled to the static unemployment status of partners as a sensitivity check and find the probability of labour force participation of married women falls if their partners are unemployed. Albeit statistically significant, it is argued that this result is predominately due to the idea that people tend to get married to other people of similar socio-economic, religious and ethnic backgrounds (known as assortative mating) which masks the addWE. This approach is thus shown to be inappropriate for the analysis of the addWE.